Flat sheet metal girders with very thin metal web. Part I, - Wagner, Herbert, 1900-1982 ([National Advisory Committee for Aeronautics], 1931)
The object of this report was to develop the structural method of sheet metal girders and should for that reason be considered solely from this standpoint. The ensuing methods were based on the assumption of the infinitely low stiffness in bending of the metal web. This simplifies the basis of calculations to such an extent that many questions of great practical importance can be examined which otherwise cannot be included in any analysis of the bending stiffness of the buckled plate. This report refers to such points as the safety in buckling of uprights to the effect of bending flexibility of spars, to spars not set parallel, etc. -- Provided by publisher.
Translation of: Ebene Blechwandträger mit sehr dünnem Stegblech.
Reprinted from "Zeitschrift für Flugtechnik und Motorluftschiffahrt, volume 20 ..., 1929, Verlag von R. Oldenbourg, München-Berlin."
Keywords: Sheet-metal -- Testing.; Airplanes -- Sheet-metal work.; Airplanes -- Design and construction.; elektronické knihy; electronic books